Ocupação e dinâmica socioambiental da sub-bacia hidrográfica do rio Cotinguiba/SE - Santos, Wesley Alves dos (2012)
The environmental analysis, with the object of study watersheds contributes to the development of a new concept in the treatment of environmental issues and serves as an aid in making decisions regarding the preservation and implementation of policies for sustainable development. In this sense, the study of the hydrographic basin of the Rio Cotinguiba, is based on its political, economic, social and cultural benefit to the state of Sergipe, since knowledge of geo-environmental scenarios contained in its area of coverage is an effective means in the pursuit of fitness for the planning and organization of geographic space. Based on geosystems approach, adapted to local conditions, this study aims, among other things, analyze the Occupation and Environmental Dynamics of Sub-River Basin Cotinguiba, but without losing sight of the analysis of the historical process of occupation and use of space in previous centuries. To achieve the goals, we used different procedures relating to literature surveys, mapping and field. Thus, there was, among other results, that the socioeconomic development of the basin did not occur in a sustainable manner and as a consequence, this fact committed to quality of life for much of its population due to socio-environmental problems, such as water supply , environmental degradation resulting from the misuse of natural resources and soil management, and the precariousness of the sewage system and deforestation found in all municipalities that make up the sub-basin dating from the colonial process.